STABILITAS EKONOMI INDONESIA DALAM PANDEMI COVID-19 DAN POTENSI INDONESIA UNTUK TERJEBAK MIDDLE INCOME TRAP - Vellix Wanggai; Mariane Olivia Delanova; Yanyan Mochamad Yani (Jurnal Academia Praja, 2023)
This article will focus on the impact of the Covid-19 pandemic on Indonesia's economic conditions. Researchers realize that solid economic stability will lead the country to achieve public welfare and achieve the ideal form of government, therefore research on the impact of the pandemic on the economic stability of a country is something important to do. The decline of Indonesia's status to a lower middle income country in mid-2021 has become a clear warning for Indonesia to improve in handling Covid-19, poor handling will have implications for the wheels of the Indonesian economy which may plunge Indonesia into a middle income trap. The results of the study show that the transformation of the economy towards a knowledge-based economy will be the right step to maintain economic stability during the pandemic because of its more resilient nature.